Groupthink Reconsidered - Whyte, Glen (Academy of Management Review, 1989)
History and the daily newspaper provide examples of policy decisions made by groups that resulted in fiascoes. The making of such decisions is frequently attributed to the groupthink phenomenon. A different perspective on the occurrence of policy fiascoes, prospect polarization, is offered. This approach employs, in addition to the pressures for uniformity of groupthink, the notions of framing effects, risk seeking in the domain of losses, and group polarization. The applicability of these theoretical mechanisms to several notorious decision fiascoes, past and present, is discussed.